Effect Of Ground Motion On Seismic Design Of Low To Medium Rise Infilled Moment Resisting Concrete Frame - Yazid, Muhammad Amar Firdauz (Universiti Sains Malaysia, 2018)
Infilled structural frames are widely used across the world including high seismicity regions. The infills are usually considered as non-structural elements and not included in the analytical and design procedure. The main objective for this study is to evaluate the performance 2D moment resisting concrete frame (MRCF) with and without infill walls under seismic provision. Non-linear static and dynamic analysis had been used in this study to evaluate the performance of low-rise to medium rise reinforced concrete building. Three different number of storey, N: 3, 6, and 9 with different infill configuration were used as the structural models. SAP200 software was used to analyse all the structural models. From the analysis conducted, pushover analysis shown that nine storey infilled frame has highest base shear force compared to three and six storey for both infilled and bare frame. Non-linear dynamic analysis has been conducted by employing five single ground motion data to represent a real seismic ground motion. Displacement curve from the analysis shown that the presence of infills reduce the displacement of structural frame. Inter-storey drift ratio (IDR) shown that deformation usually occurs at lower storey as it has higher percentage of IDR.